Magnesium Vapor Reduction of Structured Silica for Lithium Ion Battery Applications. Issue 1643 (12th March 2014) - Cook, Rob; Schrandt, Matthew; Kolla, Praveen; Rhine, Wendell; Koodali, Ranjit; Smirnova, Alevtina
ABSTRACT: Three types of silica materials with different morphology, specifically SiO2 hollow microspheres, mesoporous silica, and silica aerogel were tested as potential precursors for synthesis of silicon nano- and meso-structures that resemble the original morphology of the precursors. In the optimized magnesium thermal reduction process, magnesium vapor was delivered to silica surface through a stainless steel mesh placed on top of a zirconia boat filled with silica precursor. This approach allowed for better control of silicon nanostructure formation by minimizing reaction by-products that can affect performance of lithium ion battery anode. Material morphological properties of the reduced silica precursors are discussed in terms of X-ray diffraction, BET, BJH pore size distribution, Raman spectroscopy, and TGA.